2012
DOI: 10.2214/ajr.11.6923
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Value of Contrast-Enhanced MRI in the Detection of Biopsy-Proven Local Recurrence of Prostate Cancer After Radical Prostatectomy: Effect of Reader Experience

Abstract: OBJECTIVE The purpose of this study is to retrospectively assess the incremental value of contrast-enhanced MRI (CE-MRI) to T2-weighted MRI in the detection of postsurgical local recurrence of prostate cancer by readers of different experience levels, using biopsy as the reference standard. MATERIALS AND METHODS Fifty-two men with biochemical recurrence after prostatectomy underwent 1.5-T endorectal MRI with multiphase contrast-enhanced imaging and had biopsy within 3 months of MRI. Two radiologists (reader … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 31 publications
1
45
0
1
Order By: Relevance
“…Although prostate MR imaging offers the potential to assist clinical management of prostate cancer, MR images of the prostate can be difficult to interpret, with challenges in interreader variability repetitively documented in the literature (17)(18)(19). In other organs, standardized interpretation schemes that incorporate fixed criteria for stratifying risk of malignancy have been developed in an effort to improve consistency of interpretations among radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Although prostate MR imaging offers the potential to assist clinical management of prostate cancer, MR images of the prostate can be difficult to interpret, with challenges in interreader variability repetitively documented in the literature (17)(18)(19). In other organs, standardized interpretation schemes that incorporate fixed criteria for stratifying risk of malignancy have been developed in an effort to improve consistency of interpretations among radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…However, only limited data on the utility of 11 Ccholine PET/CT regarding the detection of local recurrence after RP are available in the literature (4,5). Conversely, the combination of T2-weighted imaging and dynamic contrast-enhanced (DCE) MR imaging with endorectal coil has been shown to have an 84%-97% sensitivity and 74%-89% specificity for detecting local recurrence in the prostatectomy bed (6)(7)(8). However, the diagnostic performance of MR imaging for metastasis to pelvic LN and bone was not addressed in these studies.…”
mentioning
confidence: 99%
“…The effect of reader experience on the incremental value of MRI/PET will require further investigation and validation. Previous studies have suggested that combining anatomical MRI with other MRI techniques (eg, contrast-enhanced and diffusion-weighted MRI) may improve the diagnostic accuracy of less experienced readers and thereby improve interreader agreement 16,17 ; the addition of PET to anatomic MRI may have a similar effect.…”
Section: Discussionmentioning
confidence: 99%